Improved Thematic Learning Outcomes of My Daily Task Sub-Themes at School Using Concrete Media for Class II Students of SDN 3 Pengadegan Wangon - Nugroho, Hasan Dwi (Universitas Sebelas Maret, 2020)
The purpose of this research is to improve the thematic learning outcomes of my daily tasks at school by using concrete media. This research is a classroom action research (PTK) which is carried out in three cycles consisting of planning, implementing, observing and reflecting. The subjects of this study were students of class II SDN 3 Pengadegan Banyumas in the 2020/2021 school year, totaling 20 students. Data collection techniques using tests. Data analysis includes data reduction, data presentation, and drawing conclusions. Research shows that the application of concrete media is very significant in improving student learning outcomes in class II SDN 3 Pengadegan, Wangon District, Banyumas Regency in the academic year 2020/2021 as evidenced by the completeness of learning outcomes 100% with an average value of 98 in cycle III.